Respuesta del cultivo de tomate lycopersicum sculentum mill variedad floradade a la fertilización orgánica en el cantón Piñas - Vicent Matamoros, Willian Geovanny (2008)
The present investigation on the response of the tomato crop (Lycopersicum sculentum Mill) variety floradade to the organic fertilization in the Canton Piñas, was carried out in the farm San Roque, belonging to the Canton Piñas, located in the road to Zaruma. The outlined objectives were: 1. to evaluate the response from the tomato crop to the organic fertilization; 2. to establish the treatment of more production and 3. to carry out the economic analysis of the treatments. Were used as organic fertilizers: Worm humus, Biol, Algreen, Humimax and absolute chek that were applied 15 days apart, the first fertilizer was applied in a dose of 250 g around the plant, while the Biol, Algreen and Humimax 30 cc per l. of water, to foliate and to the soil; the treatments were distributed in a design of Blocks at random with three replications. The evaluated variables were; days to germination, days to flowering, days to the fructification, number of fruits, circumference and weight of the fruit. The average comparison was carried out by using the test of Duncan 5%. The highest yields were for the worm humus and Humimax, being established that the tomato cultivation responded to the organic fertilization, in comparison to the check that registered the smallest yield in kg/ha, because of the micro organisms it that, allow to improve the texture of the soil and pH, the action of the micro organisms influenced in the profitability of these treatments.